Comparison of the Bioactive Properties of Honey Proteins from Floral Sources in Indonesia - Jaya, Firman; Evanuarini, Herly; Susanto, Edy; Azkarahman, Aldyon Restu (Faculty of Animal Science, Universitas Brawijaya, 2024)
The diversity of plant species in Indonesia has resulted in a wide variety of floral honey. The antioxidant activities of these Indonesian honeys have not been determined. Ten types of honey from indigenous Indonesian sources (9 monofloral; 1 heterofloral) were evaluated for their antioxidant activity using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging method. The Folin-Ciocalteu test was used to determine the total phenolic content, and an aluminum chloride colorimetric assay was used to determine the total flavonoid content. SDS–PAGE was used to determine the molecular weights of the honey proteins. The mean antioxidant activity of the honey samples, defined as the IC50 of DPPH, ranged from 5.46 to 34.42. The mean total phenol content ranged from 27.57 to 53.85 mg GAE/100 g, and the mean flavonoid content ranged from 3.58–15.67 mg CE/100 g. A protein of 60 kDa was detected in all honey varieties. A positive correlation was observed between antioxidant activity, total phenols, and total flavonoids, indicating that their phenolic and flavonoid components confer the antioxidant activity of these honey varieties. To the best of our knowledge, indigenous Indonesian honey, especially monofloral Calliandra honey, has shown greater antioxidant activity than other kinds of honey worldwide.